Improving Radiation Awareness and Feeling of Personal Security of Non-Radiological Medical Staff by Implementing a Traffic Light System in Computed Tomography - Heilmaier, C.; Mayor, A.; Zuber, N.; Fodor, P.; Weishaupt, D. (RöFo : Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebende Verfahren, 2016)
Abstract Purpose: Non-radiological medical professionals often need to remain in the scanning room during computed tomography (CT) examinations to supervise patients in critical condition. Independent of protective devices, their position significantly influences the radiation dose they receive. The purpose of this study was to assess if a traffic light system indicating areas of different radiation exposure improves non-radiological medical staff’s radiation awareness and feeling of personal security. Material and Methods: Phantom measurements were performed to define areas of different dose rates and colored stickers were applied on the floor according to a traffic light system: green = lowest, orange = intermediate, and red = highest possible radiation exposure. Non-radiological medical professionals with different years of working experience evaluated the system using a structured questionnaire. Kruskal-Wallis and Spearman’s correlation test were applied for statistical analysis. Results: Fifty-six subjects (30 physicians, 26 nursing staff) took part in this prospective study. Overall rating of the system was very good, and almost all professionals tried to stand in the green stickers during the scan. The system significantly increased radiation awareness and feeling of personal protection particularly in staff with ≤ 5 years of working experience (p < 0.05). The majority of non-radiological medical professionals stated that staying in the green stickers and patient care would be compatible. Knowledge of radiation protection was poor in all groups, especially among entry-level employees (p < 0.05). Conclusion: A traffic light system in the CT scanning room indicating areas with lowest, in-termediate, and highest possible radiation exposure is much appreciated. It increases radiation awareness, improves the sense of personal radiation protection, and may support endeavors to lower occupational radiation exposure, although the best radiation protection always is to re-main outside the CT room during the scan. Key Points: • A traffic light system indicating areas with different radiation exposure within the computed tomography scanner room is much appreciated by non-radiological medical staff. • The traffic light system increases non-radiological medical staff’s radiation awareness and feeling of personal protection. • Knowledge on radiation protection was poor in non-radiological medical staff, espe-cially in those with few working experience. Citation Format: • Heilmaier C, Mayor A, Zuber N et al. Improving Radiation Awareness and Feeling of Personal Security of Non-Radiological Medical Staff by Implementing a Traffic Light System in Computed Tomography. Fortschr Röntgenstr 2016; 188: 280 – 287